The Application of Outdoor Learning Integrated CPS Models to Improve Mathematics Learning Outcomes Students of SMA Negeri 4 Pekanbaru - Citra Aries (UIR PRESS, 2018)
Research is motivated by low mathematics learning outcomes. This study aims to improve the learning process and improve the mathematics learning outcomes of students public high school 4 Pekanbaru academic year 2017/2018 through the application of the outdoor learning integrated CPS Model. This research is a classroom action research that the teacher plays a direct role in the learning process. Subjects in this study were students of class XII IPS 1, SMA Negeri 4 Pekanbaru consists of 36 students and the object of this research is to increase the learning outcomes of mathematics with the integrated outdoor learning CPS Model. Based on the average results of students' mathematics learning tests on the cycle I was 77.09 and cycle II was 82.5 which experienced a significant increase, so based on the results of the obtained data analysis it can be concluded that the application of integrated outdoor learning CPS can improve students' mathematics learning outcomes in class XII IPS 1 SMA Negeri 4 Pekanbaru. Key word : Creative Problem Solving, Outdoor Learning, Learning Outcome, Classroom Action Research